2016
DOI: 10.1007/s12010-016-2084-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Proteins with Stimulating Activity on Ovarian Estradiol Biosynthesis from Four Different Dioscorea Species in vitro Using Both Phenotypic and Target-based Approaches: Implication for Treating Menopause

Abstract: Rhizomes of Dioscorea species are traditionally used for relieving menopausal syndromes in Chinese medicine. The estrogen-stimulating bioactive principles have been demonstrated in our previous study. In this study, the estrogen-stimulating effects of proteins isolated from four Dioscorea species [D. alata L. (DA), D. zingiberensis C.H. Wright (DH), D. collettii var. hypoglauca (Palib.) S.J. Pei & C.T. Ting (DH), and D. oppositifolia L. (DO)] have been investigated and compared. Microscopic authentication of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…In traditional medicine, wild yam is widely used to treat menopausal symptoms, most likely due to its phytoestrogen content and corresponding ability to stimulate ovarian estradiol synthesis [109][110][111]. In one study [112], twenty-four healthy postmenopausal women replaced their staple food of rice with 390 grams of yam or sweet potato (control) in two of the three meals per day for thirty days.…”
Section: Wild Yam (Dioscorea)mentioning
confidence: 99%
“…In traditional medicine, wild yam is widely used to treat menopausal symptoms, most likely due to its phytoestrogen content and corresponding ability to stimulate ovarian estradiol synthesis [109][110][111]. In one study [112], twenty-four healthy postmenopausal women replaced their staple food of rice with 390 grams of yam or sweet potato (control) in two of the three meals per day for thirty days.…”
Section: Wild Yam (Dioscorea)mentioning
confidence: 99%
“…The active fraction of GJE and its major compounds were also investigated. With the combination of the major compounds from the active fraction and possible active ingredients from network pharmacology, phenotypic (estrogen-stimulating effect) and target-based (aromatase/FSHR/StAR/ERα/ERβ) methods were used to find the active components of GJE (Lu et al, 2016 ). Phenotypic approaches play a crucial role in drug discovery because data from the large-scale drug screening and target-based approaches suggest the relationships between a potential new drug and its molecular targets (Gilbert, 2013 ; Swamidass et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The major components were then extracted from the bioactive fraction and converged with the probable active ingredients predicted by network pharmacology. Among these components, phenotypic (based on the estradiol assay) and target-based (based on the molecular docking analysis, Western blot assay and FSHR inhibition assay) drug-screening principles were applied to screen bioactive compounds with estrogen-stimulating effects (Hughes et al, 2011 ; Lu et al, 2016 ). Breast cancer cells were also used to pre-evaluate the cancer risk of GJE active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, recent report found that glycyrrhizae radix, cinnamomi cortex, Evodiae fructus, and Zingiberis rhizoma demonstrate ER β -dependent estrogenic activity and their combined use could produce synergistic ER β -dependent estrogenic activity [ 51 ]. In addition, the estrogen-stimulating bioactive proteins isolated from Dioscorea species could upregulate the protein expression of ER β and its translational levels, potentially reducing the risk of ovarian cancer [ 52 ]. These results scientifically support the traditional use of Chinese medicine for relieving menopausal syndrome or treating other female aging disorders, and progress in analysis techniques [ 53 ] would widely spread its potential clinical use in the future.…”
Section: Discussionmentioning
confidence: 99%